Mitochondrial dysfunction and beneficial effects of mitochondria-targeted small peptide SS-31 in Diabetes Mellitus and Alzheimer's disease. (September 2021) - Ding, Xiao-Wen; Robinson, Megan; Li, Rongzi; Aldhowayan, Hadeel; Geetha, Thangiah; Babu, Jeganathan Ramesh
Abstract: Diabetes and Alzheimer's disease are common chronic illnesses in the United States and lack clearly demonstrated therapeutics. Mitochondria, the "powerhouse of the cell", is involved in the homeostatic regulation of glucose, energy, and reduction/oxidation reactions. The mitochondria has been associated with the etiology of metabolic and neurological disorders through a dysfunction of regulation of reactive oxygen species. Mitochondria-targeted chemicals, such as the Szeto-Schiller-31 peptide, have advanced therapeutic potential through the inhibition of oxidative stress and the restoration of normal mitochondrial function as compared to traditional antioxidants, such as vitamin E. In this article, we summarize the pathophysiological relevance of the mitochondria and the beneficial effects of Szeto-Schiller-31 peptide in the treatment of Diabetes and Alzheimer's disease. Graphical Abstract: ga1